DEVELOPMENT OF CITIZENS' CREATIVE COMPETENCE THROUGH COLLABORATION OF CITIZENSHIP SITES - Rendra, Agus (Universitas Pendidikan Indonesia (UPI), 2022)
Creativity developing is an effort competence enhancement of citizens and part of the educational community means in order to have creative culture and always been learners community. Linggawastu as a society of Bandung which was part of a global citizen has great potential for creating a progress for Indonesia. Bandung Creative City Forum is the site of citizenship agent taking the role of strategic in implement one of the three dimensions of Citizenship Education that is socio-cultural Education. BCCF became agent in the development of competence Linggawastu residents and instituted creative character through three program, namely Capacity Building, Y-PLAN, and Creative Class